Hormesis effect of UV-S irradiation on pigment complex and antioxidant enzymes of cells in leaves of Pisum sativum L. - Mikhyeyev, A.N.; Zhuk, V.V.; Ovsyannikova, L.G.; Grodzinsky, D.M. (Reports of the National Academy of Sciences of Ukraine, 2016)
The hormesis effect of UV-C irradiation on pigments, endogenous hydrogen peroxide content, and antioxidant enzyme activity of pea leaves is studied. It is established that, after the irradiation of plants by an adapted dose of UV-C, the level of endogenous H2O2 decreases. Determination of the activity of ascorbate peroxidase and catalase has established the stimulation of antioxidant enzymes after the action of UV-C. The chlorophyll content in leaves after the effect of adaptive UV-C radiation is stabilized and subsequently restored. It is shown that UV-C irradiation on pea leaves in an adaptive dose increases the tolerance of plants to the repeated UV-C irradiation.